Hippocampal-Prefrontal cortex network dynamics predict performance during retrieval in a context-guided object memory task - Morici, Juan Facundo (2021)
Remembering life episodes is a complex process that requires the interaction between multiple brain areas. It is thought that contextual information provided by the hippocampus (HPC) can trigger the recall of a past event through the activation of medial prefrontal cortex (mPFC) neuronal ensembles, but the underlying mechanisms remain poorly understood. Indeed, little is known about how the vHPC and mPFC are coordinated during a contextual-guided recall of an object recognition memory. To address this, we performed electrophysiological recordings in behaving rats during the retrieval phase of the object-in-context memory task (OIC). Coherence, phase locking and theta amplitude correlation analysis showed an increase in vHPC-mPFC LFP synchronization in the theta range when animals explore contextually mismatched objects. Moreover, we identified ensembles of putative pyramidal cells in the mPFC that encode specific object-context associations. Interestingly, the increase of vHPC-mPFC synchronization during exploration of the contextually mismatched object and the preference of mPFC incongruent object neurons predicts the animals’ performance during the resolution of the OIC task. Altogether, these results identify changes in vHPC-mPFC synchronization and mPFC ensembles encoding specific object-context associations likely involved in the recall of past events.